The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00249-015-1071-4
|View full text |Cite
|
Sign up to set email alerts
|

Arginine-, d-arginine-vasopressin, and their inverso analogues in micellar and liposomic models of cell membrane: CD, NMR, and molecular dynamics studies

Abstract: We describe the synthesis, pharmacological properties, and structures of antidiuretic agonists, arginine vasopressin (AVP) and [d-Arg8]-vasopressin (DAVP), and their inverso analogues. The structures of the peptides are studied based on micellar and liposomic models of cell membranes using CD spectroscopy. Additionally, three-dimensional structures in mixed anionic–zwitterionic micelles are obtained using NMR spectroscopy and molecular dynamics simulations. NMR data have shown that AVP and DAVP tend to adopt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 90 publications
(105 reference statements)
1
13
0
Order By: Relevance
“…In summary, addition of the liposomes to the water differentiated the shapes of the CD spectra of vasopressin‐like peptides. Results of our recent studies confirmed the previously ones, that the smallest differences occurred with zwitterionic DPPC, the largest‐with anionic DPPG, and intermediate ones‐with mixed anionic‐zwitterionic liposomes. Moreover, upon increasing the negative charge at the liposomes surface, the intensity of 227‐nm band increases for both strong antidiuretic agonists, dAVP and dDAVP, especially for the more selective latter one.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…In summary, addition of the liposomes to the water differentiated the shapes of the CD spectra of vasopressin‐like peptides. Results of our recent studies confirmed the previously ones, that the smallest differences occurred with zwitterionic DPPC, the largest‐with anionic DPPG, and intermediate ones‐with mixed anionic‐zwitterionic liposomes. Moreover, upon increasing the negative charge at the liposomes surface, the intensity of 227‐nm band increases for both strong antidiuretic agonists, dAVP and dDAVP, especially for the more selective latter one.…”
Section: Resultssupporting
confidence: 89%
“…In addition, with dAVP and dDAVP the 268‐nm band does not show two distinct shoulders in contrast to those in aqueous environment and the inverso analogs in lipid solution. In the long‐wavelength CD spectra of vasopressin‐like peptides, a slight inflection in the CD curve in water emerges around 250 nm, which completely disappears in the liposome solution . The same pattern has now been followed with both dAVP and dDAVP.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…The starting coordinates of the DPC micelle-water system were taken from simulations conducted by Tieleman et al [36]. A single molecule of DPC was constructed on the basis of previously published parameters [37,38]. The pre-built hydrated DPC micelle consisted of 65 DPC monomers and 6305 water molecules.…”
Section: Construction Of Peptides In Dpc Micelle and MD Simulationsmentioning
confidence: 99%